The ANALISIS EFEK KOMPONEN PARASITIK TERHADAP KINERJA FILTER EMI DALAM RANGKA MEMITIGASI EMISI RADIASI - Tiva Aresta; Mohammad Yanuar Hariawan (Politeknik Caltex Riau, 2021)
To reduce conduction and radiation emissions in electronic devices can use EMI filters. However, the use of EMI filters can also cause the parasitic appearance of the components used in the filter. Parasitic components can cause spikes in radiation emissions as well as conduction at high frequencies. To minimize the surge in radiation emissions in the filter circuit, several steps can be applied, namely providing shielding, ground plane, and also adjusting the layout of components on the printed circuit board (PCB). The purpose of this study was to look at the efficiency of the EMI passive filter circuit that will be applied to LED lights in dampening the radiation emissions produced by LED lights. Size is done in two-room conditions when many measurements are taken and when the room is used only to measure radiation emissions. The measurement results showed the EMI filter with the addition of shielding and a distance of 5 mm between the inductor and capacitor used resulted in a difference of 0.4 dBμV with an EMI filter with additional shielding and ground plane. Emissions produced by lights before and after are given shielding, ground plane, and the addition of distance between components does not exceed the CISPR limit of 11.